2017
DOI: 10.12962/j20882033.v28i3.3217
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Risk Factors in the Project of Oil and Gas Industry

Abstract: Abstract In Each activity in the oil and gas industry there are risks that could hamper the project and also there is a huge risk to the environment, social and economic. Besides oil and gas industry projects also have the potential to be dangerous to life, property and the environment, the hazard can occur if the activity is not controlled and regulated by appropriate. Basically, the disaster is certainly not possible to be planned and can occur at any time. But the circumstances of a disaster can be anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Examining the research background in the field of risk management of oil and gas projects reveals that few studies have been conducted so far in the field of risk assessment compared to construction projects (Rodhi et al, 2017). On the other hand, these studies have assumed normal conditions and there is no research on the risks caused by the sanctions on oil and gas projects; also, in studies conducted to assess and evaluate risks, the relationships between the risks and their influence on each other are not considered at leveling and prioritization although it is a Interactive risk assessment in projects very important issue (Fang et al, 2017).…”
Section: Findings and Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the research background in the field of risk management of oil and gas projects reveals that few studies have been conducted so far in the field of risk assessment compared to construction projects (Rodhi et al, 2017). On the other hand, these studies have assumed normal conditions and there is no research on the risks caused by the sanctions on oil and gas projects; also, in studies conducted to assess and evaluate risks, the relationships between the risks and their influence on each other are not considered at leveling and prioritization although it is a Interactive risk assessment in projects very important issue (Fang et al, 2017).…”
Section: Findings and Results Analysismentioning
confidence: 99%
“…A review of the research works on the risk management of oil and gas projects demonstrates that few studies have been conducted so far in the field of risk assessment of oil and gas projects (Rodhi et al , 2017). The important issue of the relationship between risks has not been considered in previous studies (Fang et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to adopt or apply more extensive theories, models and risk management frameworks because of the complex nature of the oil and gas business and complicated risk factors (Suda et al, 2015). Oil and gas projects are large and complex, use state-of-the-art technology, involve multiple stakeholders and require analysis from various aspects, including sustainable development (Rodhi et al, 2017;Dey, 2012). Oil and gas projects are exposed to multiple external risk factors such as economic, political and government stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By examining the related literature on the risk management of oil and gas projects, we found that a few studies have been conducted in the field of risk assessment of oil and gas projects [6]; however, the conducted studies have not taken the interactions between the risks and possible scenarios in the project environment into account [7]. Thus, due to the special importance of achieving project goals in oil and gas industry and the domino effects of the occurrence of risks, we first identify the goals and risks of the project of gas condensate storage tank construction (G.C.S.T.C) as one of the significant projects in oil and gas industry and then develop a model in a dynamic framework so as to fully investigate the reasons for risk occurrences and simulate the risk of reaching the project goals over the project life cycle.…”
Section: Introductionmentioning
confidence: 99%